Optimal management of power networks using a dynamic line rating approach - Duque, Joaquim (2018)
ABSTRACT: Due to the stochastic nature of wind, the wind power integration into the power system poses serious challenges to the transmission system operators (TSO). The impact of large amounts of wind energy generation onto the power system may congest some of the transmission lines that transport it to the (sometimes) distant consumption centres. Since the occurrence of wind not only contributes to the loading of the connecting electric line, but also increases the line capacity, via convective cooling of the cables, a dynamic line rating (DLR) analysis computes a more realistic set of values for the line capacity, thus it can be a cost-effective solution to alleviate some overhead line congestion problems. This work presents an operational tool for the DLR analysis of power networks, allowing the optimal integration of renewable energy sources, especially where potentially congested lines may exist. The tool was applied to a real case study using forecast meteorological data, and the results achieved were compared with those obtained by using the Portuguese TSO method for assessing the transmission capacity of the lines. For high wind speed conditions, results show a noticeable increase on the cable’s convective cooling assessed by the DLR analysis. This assessment leads to a noticeable rise on the cables’ capacities that overcame the congestion associated with the high injection levels of wind power generation in the power grid.